Pemberian Mikroorganisme Selulolitik dan Pupuk Anorganik Untuk Pertumbuhan Kelapa Sawit (Elaeis guineensis jacq.) Tbm-III - Ondo Sijabat; Gusmawartati '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Research has been conducted to determine the influence of the interaction of selulolitik microorganisms and the granting of inorganic fertilizers for growing oil palm (Elaeis guineensis Jacq.) TBM-III. This research was carried out in a single PT. Tunggal Perkasa Plantation in the Air Molek, sub-district Pasir Penyu, District Indragiri Hulu-Riau, starting from February to June. Research using Random Design Group (RAK) and two factors. The first factor is the dose of microorganism selulolitik consists of two levels (0 and 20 ml/plant) and inorganic manures dosage consists of three levels (1, ½ and ¼  dosage recommendations/plant). A combination of treatment between these 2 factors is a combination of 6 with 3 replicates, so that the experiment was a total of 18 units. The Data were analyzed using analysis of variance (ANOVA) and in advanced trials Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The results show a combination of MOS 20 mL/plant and the granting of ¼ x inorganic fertilizers on crops dose Palm in TBM-III shows the interaction of the granting of MOS and inorganic fertilizers best parameter on added rod ring, the length of the rachis, long petiola and the width of the child leaves.   Keywords: Oil Palm, Mikroorganism Selulolitic (MOS) and Inorganic Fertilizers.